Екологічна оцінка сучасного стану якості води річок Західного Полісся - Нетробчук, Ірина Марківна; Netrobchuk, Iryna M. (Волинський національний університет імені Лесі Українки, 2007)
Визначена екологічна оцінка сучасного стану поверхневих вод Західного Полісся. В контрольних пунктах спостережень показана якість води, виражена значеннями блокових та інтегрального індексів. Визначено відповідність якості води річок екологічним нормам. Встановлено джерела їх забруднення та клас якості води.

Ecological assessment of the current state of surface water quality of the Western Polysya is carried out. The water quality in observation points described by block and integrated indices. The surface water quality correspondence with ecostandards is determined. The sources of their pollution and class of water’s quality are indicated.
Ecological assessment of the current state of rivers water quality of the Western Polysya
Keywords: оцінка якості води; індекс забруднення; джерело забруднення; клас якості води; показники; методи; evaluation of water’s quality; an index of pollution; a source of pollution; class of water’s quality; indexes; methods